Immunoexpression of p38 Mitogen-Activated Proteinkinase in Patients with Aggressive and Chronic Periodontitis. (January 2013) - Uraz, A.; Ayhan, E.; Yildirim, B.; Bariş, E.; Pehlivan, S.; Eren, K.
The influence of p38 mitogen-activated proteinkinase (MAPK) expression in the development and progression of periodontal disease is currently under investigation. The aim of the present study is to investigate whether the p38 MAPK expression in gingival tissues correlates with IL-1β levels in gingival crevicular fluid (GCF). Twenty patients with generalized aggressive periodontitis (GAgP), 15 patients with generalized chronic periodontitis (GCP) and 10 healthy subjects (H) were enrolled in the study. Clinical data, gingival tissue biopsies and GCF samples were collected. The expression of p38 was investigated by immunohistochemistry. The levels of IL-1β in GCF were measured using ELISA. Mean clinical parameters and GCF volumes were statistically higher in patients with GAgP and GCP compared to H subjects. Higher levels of IL-1β were found in both periodontitis groups. The p38 expression was significantly increased in inflamed gingival tissues. There were no statistically significant differences in levels of IL-1β and p38 expression between subjects with GAgP and GCP. Our data support the hypothesis that MAPK signaling pathway is an additional player in the pathogenesis of periodontitis. This is the first report to evaluate the involvement of p38 MAPK in patients with GAgP and GCP which might be, in part, considered of value in understanding disease mechanisms.